2010
DOI: 10.1002/adma.200904155
|View full text |Cite
|
Sign up to set email alerts
|

High‐Efficiency Solar Cell with Earth‐Abundant Liquid‐Processed Absorber

Abstract: Chalcogenide-based solar cells provide a critical pathway to cost parity between photovoltaic (PV) and conventional energy sources. Currently, only Cu(In,Ga)(S,Se) 2 (CIGS) and CdTe technologies have reached commercial module production with stable power conversion efficiencies of over 9 percent. [1,2] Despite the promise of these technologies, restrictions on heavy metal usage for Cd and limitations in supply for In and Te are projected to restrict the production capacity of the existing chalcogen-based techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
772
1
4

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 1,087 publications
(797 citation statements)
references
References 26 publications
20
772
1
4
Order By: Relevance
“…Zn-rich (Zn/Sn ~ 1.36), which is consistent with the stoichiometry of the best CZTS solar cells reported in the literature [11,12]. The Cu/(In+Ga) ratio for our reference CIGS is ~ 0.9 and the Ga/(In+Ga) ~ 0.3, as required for record performance [13].…”
Section: Introductionsupporting
confidence: 70%
“…Zn-rich (Zn/Sn ~ 1.36), which is consistent with the stoichiometry of the best CZTS solar cells reported in the literature [11,12]. The Cu/(In+Ga) ratio for our reference CIGS is ~ 0.9 and the Ga/(In+Ga) ~ 0.3, as required for record performance [13].…”
Section: Introductionsupporting
confidence: 70%
“…23 Moreover, Cu 2 ZnSnS x Se 4-x -based thin-film solar cells with power conversion efficiency of 9.6%, a level suitable for possible commercialization, have been constructed by solution method using toxic and unstable hydrazine. 24 However, solution-based methods for synthesis of highquality and stoichiometric CZTSe NCs is still a big challenge. 25,26 On the other hand, it is well known that the composition and structure of NCs significantly affect their optical and electrical properties, and the structure can be tuned by source materials, capping ligands, as well as synthetic temperature.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] In addition to these properties, its toxicity is relatively low compared to the compounds containing selenium such as Cu 2 Zn 1−x Cd x Sn(Se 1−y S y ) 4 , Cu 2 ZnSn(Se,S) 4 , Cu(In,Ga)Se 2 , and CdTe so that it is very attractive as a light absorber material for solar cells. [4][5][6][7][8] Several research efforts have recently been made on the CZTS-based solar cells since Katagiri et al reported a CZTS/CdS hetrojunction solar cell with 6.77%. [9][10][11][12][13][14][15] However, an intensive usage of highly toxic cadmium compound such as CdS, prohibited by the RoHS (Restriction of the use of certain Hazardous Substances in electrical and electronic equipment) regulations, is a drawback and an alternative material is desirable to realize a more environment-friendly device.…”
Section: Introductionmentioning
confidence: 99%